Business Strategy And Social Media On Customer Satisfaction In The Barbershop Business - Meutia, Riza Fanny (CV. Pusdikra Mitra Jaya, 2025)
This study aims to determine and analyze business strategies and social media on customer satisfaction at the barber house business in Medan. The population of this study amounted to 40 customers of Barber shop. The number of samples was 40 customers of Barber shop with saturated sampling technique. This research data was obtained from interviews and distributing research questionnaires to customers of Barber shop. The analysis technique uses multiple linear regression analysis. The results of this study indicate that simultaneously business strategy and social media have a positive and significant effect on customer satisfaction at the Barber shop business in Medan city. Partial research results show that business strategy and social media each have a positive and significant effect on customer satisfaction at the Barber shop business In Medan city.